Preserving Indigenous Heritage: A Strategic Roadmap for Community Based Cultural Development - Zussette Candelario-Aplaon (Advanced Qualitative Research, 2025)
The Philippines is home to a diverse array of indigenous people, with unique languages, cultures, and traditions. Despite their significant contribution to the country’s heritage and ecological balance, these communities often face marginalization and discrimination. They are among the poorest sectors of the population, illiterate, most vulnerable to extreme weather, and have limited access to basic services. To help build a sustainable community for the Indigenous people and contribute to Sustainable Development Goal 11, this study was undertaken to gather essential information that can inform policy decisions and strategic planning for the advancement of Indigenous communities. This study aims to determine the areas that could be developed in the indigenous community in southern Luzon Philippines using the Threats, Opportunities, Weaknesses, and Strengths (TOWS) matrix. Using a qualitative ethnographic method, data were collected through community immersion, participatory observation, interviews, and focus group discussions. Eighteen indigenous people belonging to the Hanunuo indigenous cultural community were selected as participants. The results show that pre-colonial script (Surat Mangyan), chanted poetry (Ambahan), and indigenous textile weaving (Ramit) are still being practiced by the elders. However, the younger generation prioritizes livelihood over cultural preservation, which would lead to the extinction of this intangible cultural heritage. Livelihood and cultural identity are essential for community development; thus, devising programs that address both are necessary. The findings served as a basis for the formulation of a strategic community development plan serving benchmarks for government agencies, higher education institutions, and non-government organizations.